Non-surgical Treatment of Guttural Pouch Empyema with Presence of Chondroids in a Filly - Cestari, Heitor; Pereira, Isabella Barros de Sousa; Mendes, Letícia Hirata; Sousa, Nathalia Cardoso de; Souza, Joel Phillipe Costa e; Baumam, Carlos Alberto Escada; Watanabe, Marcos Jun (Acta Scientiae Veterinariae, 2020)
Background: Guttural pouch empyema in horses is a disease described by the accumulation of purulent/mucopurulent exudate, which with chronification of the disease can become chondroids, affecting horses of any age and not presenting breed predisposition. The main cause of empyema is upper respiratory infection, associated or not with failure in the defense mechanisms, as well as drainage to the guttural pouch of retropharyngeal lymph node abscesses; the main pathogen related to this condition is Streptococcus equi. This paper aims to describes a case of a filly that presented a mucopurulent nasal discharge, five months of evolution, and irresponsive to antibiotic therapy. Case: A 2.5-year-old quarter filly was referred to the veterinary hospital presenting a five months evolution mucopurulent nasal discharge, irresponsive to gentamicin and ceftiofur, and later doxycycline, acetylcysteine and clenbuterol that were instituted on the farm. Throw the endoscopic examination of the upper respiratory tract, was observed the presence of mucopurulent content and chondroids inside the right guttural pouch. This material was collected and sent for culture and antibiogram tests. Streptococcus equi was isolated, and was only sensitive to ceftiofur. The treatment included the guttural pouches flushes with warm saline solution (0.9%) associated with Lauryl Dietylene Glycol Ether Sulfate Sodium (28%) and acetylcysteine (10%). In addition to topical treatment, 5 mg/kg of ceftiofur was administered intramuscularly daily for 7 days. After 10 flushes of the guttural pouch, was observed a total absence of chondroid and mucopurulent contents. Discussion: The treatment of the guttural pouch empyema can be performed either by conservative methods or by the surgical drainage. Among the benefits of the conservative treatment are the absence of the risks related to the surgical procedure and the possibility of doing the treatment without a surgical facility. On the other hand, it usually presents a longer time to the remission of the clinical signs compared with the surgical drainage, since the mucopurulent content and the chondroids have to be disassembled and dissolved before being able to be drained from the guttural pouch. Even though, the conservative treatment is effective to a large number of cases, and with the utilization of agents to dissolve the chondroids can be performed with success in cases with a large number and size of chondroids. The surgical treatment is considered the gold standard in chronic cases, due to the difficult of removal of the chondroids with the conservative methods. The main complications related with the method are the iatrogenic lesions to noble structures present inside the guttural pouches, as cranial nerves and arteries. The decision of the treatment, surgical or conservative, must consider the risks to the patient, the facilities, and the costs of the procedure. The present study demonstrates that agents as lauryl-diethylene-glycol-ether sodium sulfate (28%) and acetyl cysteine can be effective as diluents for thick secretions and organic contents, and for that reason, increase the success of the conservative treatment of guttural pouch empyema. Consequently, improving the outcome and the rate of remission in cases of guttural pouch empyema that have a large number of chondroids, and are located remotely from referring veterinary hospitals or that cannot afford the surgical procedure.